Effects of Biology 21st Century Teaching Strategies on Students’ Motivation - Adyani Ahmad; Md Jais Ismail (PT FORMOSA CENDEKIA GLOBAL, 2023)
Malaysia national education aspirations in the Malaysian Education Blueprint (2013-2025) implies the importance of holistic and resilient talents development program in educating the new generations. Educators as facilitators are demanded to be more proactive in designing classroom activities to achieve the vision. This study investigates the 21st century classroom activities involving 4C (creativity, communication, collaboration, critical thinking) elements in high school science students which believed able to enhance students’ motivation. The sample involved 91 form 4 students and data collected using instrument adapted from MUSIC Inventory. Analysis using SPSS 21 shows significant difference in all domains; empowerment, usefulness, success, interests and caring. Overall mean difference of all domains is M= -4.98 (SD= 1.13). Dependent t-test analysis shows t= -4.2, df = 90 while p-value is 0.00 (P<0.05). The finding implies that the learning techniques adapted involving 4C elements significantly increases students’ motivation.